Compact spectral shearing interferometer for ultrashort pulse characterization. - Radunsky, A; Walmsley, I; Gorza, S; Wasylczyk, P (2007)
A simple, compact, and robust implementation of spectral shearing interferometry using a single nonlinear crystal for both ancilla generation and upconversion is demonstrated. The device is capable of accurate characterization of femtosecond laser pulses over the 740-900 nm range with a KDP crystal.